Biosynthesis of oxygenated brasilane terpene glycosides involves a promiscuous N-acetylglucosamine transferase. Issue 82 (16th September 2020) - Feng, Jin; Surup, Frank; Hauser, Maurice; Miller, Anna; Wennrich, Jan-Peer; Stadler, Marc; Cox, Russell J.; Kuhnert, Eric
Abstract : The biosynthesis of brasilane glycosides in the fungus Annulohypoxylon truncatum was investigated resulting in the characterisation of a rare type of fungal N -acetylglucosamine transferase. Abstract : Investigation of the metabolome of the ascomycete Annulohypoxylon truncatum led to the identification of novel oxygenated brasilane glycosides and the revision of the stereochemistry of the brasilane A octahydro-1 H -indene core scaffold to trans . The bra biosynthetic gene cluster containing five genes ( braA – braE ) was identified and verified by heterologous expression experiments in Aspergillus oryzae demonstrating that BraC is a multifunctional P450 monooxygenase. In vitro studies of BraB revealed it to be a very rare fungal UDP-GlcNAc dependent N -acetylglucosamine transferase. UDP-glucose is also accepted as a donor, and a broad acceptor substrate tolerance for various primary and secondary alcohols was observed.